2015
DOI: 10.1007/s10334-015-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface coil with reduced specific absorption rate for rat MRI at 7 T

Abstract: The slotted surface coil offers improved performance and low SAR100 mg for rat brain imaging at 7 T. This approach may be used with new RF coils to investigate SAR in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The structural MRI scanning procedure of each rat lasted about forty minutes. The signal to noise ratio (SNR) is an important quality control index for structural MRI studies and there exist many ways for the calculation of SNR, such as those reported by Solis-Najera et al (2015), Pohmann et al (2016). In the present study, we selected a simple but effective approach for the calculation of SNR, which is defined as the ratio of the mean image intensity in the brain divided by the standard deviation of the intensity at background (Sumiyoshi et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The structural MRI scanning procedure of each rat lasted about forty minutes. The signal to noise ratio (SNR) is an important quality control index for structural MRI studies and there exist many ways for the calculation of SNR, such as those reported by Solis-Najera et al (2015), Pohmann et al (2016). In the present study, we selected a simple but effective approach for the calculation of SNR, which is defined as the ratio of the mean image intensity in the brain divided by the standard deviation of the intensity at background (Sumiyoshi et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The electromagnetic characteristics and the spatial distribution of the magnetic field 1 produced by our coil were numerically investigated using the finite integral technique (FIT) [16]. The FIT approach has been used for electromagnetic characterization of low and high field MRI RF coils loaded with human-mimicking phantoms with great results [17].…”
Section: Electromagnetic Field Simulationsmentioning
confidence: 99%